Practice of Game Development Project-Based Learning Classes for Improving Disaster Management - Toshiya Arakawa; Shigeyuki Yamabe; Takahiro Suzuki (MDPI AG, 2023)
It is necessary to discuss from various angles how to make the younger generation, who will be responsible for future society, aware of disasters and how to cope with them. Therefore, we designed a project-based learning class, "Media Design Project III · IV", in which students are asked to create a game to raise their awareness of disaster prevention. This class aims to improve disaster awareness, especially tsunami evacuation, and to improve abilities that students will need in the future, i.e., time management and problem-solving, especially after they begin work. It was found that the game can increase tsunami evaluation awareness. Therefore, the projects presented here might become a new method for education, especially disaster education and career education, with games focused on disasters potentially being a new tool for raising awareness about disasters.